A role of serotonin and the insula in vigor: Tracking environmental and physiological resources. (30th September 2021) - Tops, Mattie; Boksem, Maarten A. S.; Montero-Marin, Jesus; van der Linden, Dimitri
Abstract: We describe a neural monitor of environmental and physiological resources that informs effort expenditure. Depending on resources and environmental stability, serotonergic and dopaminergic neuromodulations favor different behavioral controls that are organized in corticostriatal loops. This broader perspective produces some suggestions and questions that may not be covered by the foraging approach to vigor of Shadmehr and Ahmed (2020).